Candidatus Nitrosopolaris, a genus of putative ammonia-oxidizing archaea with a polar/alpine distribution - Pessi, Igor S; Rutanen, Aino; Hultman, Jenni (FEMS Microbes, 2023)
Ammonia-oxidizing archaea (AOA) are key players in the nitrogen cycle of polar soils. Here, we analyzed metagenomic data from tundra soils in Rásttigáisá, Norway, and recovered four metagenome-assembled genomes (MAGs) assigned to the genus ‘UBA10452’, an uncultured lineage of putative AOA in the order Nitrososphaerales (‘terrestrial group I.1b’), phylum Thaumarchaeota. Analysis of other eight previously reported MAGs and publicly available amplicon sequencing data revealed that the UBA10452 lineage is predominantly found in acidic polar and alpine soils. In particular, UBA10452 MAGs were more abundant in highly oligotrophic environments such as mineral permafrost than in more nutrient-rich, vegetated tundra soils. UBA10452 MAGs harbour multiple copies of genes related to cold tolerance, particularly genes involved in DNA replication and repair. Based on the phylogenetic, biogeographic, and ecological characteristics of 12 UBA10452 MAGs, which include a high-quality MAG (90.8% complete, 3.9% redundant) with a nearly complete 16S rRNA gene, we propose a novel Candidatus genus, Ca. Nitrosopolaris, with four species representing clear biogeographic/habitat clusters. Peer reviewed